(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
There are some factors causing student drop out in madrasah. testing the correlation between the number of students drop out and the factors causing student drop out conducted in 14 provinces comes to conclusion that economic social status of parents is the most dominant factor causing them dropped out. the other factors are parents’ awareness toward the importance of education, condition of student environment, student learning motivation, level of student competency (IQ), and student opportunity to get education. to lessen the number of student drop out in madrasah caused by parent economic social status, government intensively implements PKPS BBM program like BOS and BKM evenly and coincided with the target.